'Of Fairies': An Excerpt from a Seventeenth-Century Magical Manuscript. Issue 2 (3rd April 2018) - Harms, Dan
Abstract: Bodleian MS Douce 116, dating to the seventeenth century, provides us with a passage detailing beliefs about fairies written by an anonymous author. This article presents the text of the passage, along with commentary on the manuscript and a comparison of its typology of fairies with those in other period sources.